Archival Characters: Incorporating History in Thomas Pynchon’s V. and Toni Morrison’s Beloved - LeAnn Stevens-Larré (Sillages Critiques)
Drawing from the fundamental theories of archives, both literal and metaphorical, this article defines the concept of “archival character,” presenting Thomas Pynchon’s V. and Toni Morrison’s Beloved as primary examples. These characters are drawn as sites of memory where the disparate stories of the dispossessed find embodiment and thus the possibility of narrative reconstruction.